Effect of Drug Abuse Counselling Training: Adaptation of Motivational Interviewing Strategy on Empathy, Confidence, Change Behaviour Skill and Self-Esteem among Prison Officers in Sabah (Sains Humanika, 2020)
The correctional officers in Sabah Prison have not received any specific training to treat drug abusers, even though they consist the highest percentages of inmates. The Adaptation of Motivational Interviewing, AMI Treatment Modules, has been used as the training module in this project. This project aims to transfer drug abuse counselling skills to 67 prison officers in Sabah. Participants were trained for 5 days with various training methods, and the instruments used were Counseling Response Questionnaires (CRQ), Confidence and Knowledge Scale (CKS), Behavior Change Counselling Index (BECCI) and Rosenberg Self-Esteem. This study uses a quasi-experimental design aimed at seeing the effectiveness of AMI's training. Result from Wilcoxon signed-ranks test showed that the mean for post-test ranks was higher than the mean pre-test ranks for empathy (z = -7.14, p < .05, confidence ( z = -6.95, p > .05), change behavior skill (z = -5.99, p > .05) as well as self- esteem (z = -4.98, p > .05). In other words, the study showed that the Drug Abuse Counselling Training: Adaptation of Motivational Interviewing Strategy can promote positive effects on subject’ empathy, confidence, change behavior skill and self-esteem. Therefore, the five-day workshop based on the AMI Treatment Modules can be used as a guideline for relevant authorities such as the Malaysia Prison Department for future training programmes particularly to correctional officers. In conclusion, this project has been able to enhance empathy, confidence and behavior-changing skills as well as self-esteem among prison officers in Sabah.
Keywords: Motivational Interviewing; drug abuse counseling training; empathy; confidence; behaviour change.